1985
DOI: 10.1055/s-2007-969397
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lens-Aldose Reductase Activity by Brazilin and Haematoxylin

Abstract: Brazilin and haematoxylin, plant pigments, were examined for their effects on the Bovine-Lens aldose reductase (LAR)-activity. About 50% inhibition was observed in a concentration of 10 (-4) M-brazilin and 10 (-4) M-haematoxylin, and above 95% inhibition was observed in a concentration of 10 (-3) M-brazilin and 10 (-3)M-haematoxylin. In order to determine the type of inhibition, kinetic studies were also conducted with brazilin and haematoxylin, in which both were found to be noncompetitive inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…[4][5][6][7][8][9] Pharmacological studies of Sappan Lignum focusing on its vasorelaxation 10) or immunosuppressive effect 11) have concluded that 1 is the active compound. Compound 1 alone was reported to show anti-inflammatory effect, 12,13) lensaldose reductase inhibitory effect, 14) and anti-hepatotoxic effect.15) However, there are few pharmacological studies of other compounds except ours. We previously performed an in vitro assay for 1, brazilein, 2, 3, 4, and 5, and clarified such properties as inhibition of nitric oxide (NO) production and inducible NO synthase gene expression, as well as free radical scavenging and antioxidant activity.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Pharmacological studies of Sappan Lignum focusing on its vasorelaxation 10) or immunosuppressive effect 11) have concluded that 1 is the active compound. Compound 1 alone was reported to show anti-inflammatory effect, 12,13) lensaldose reductase inhibitory effect, 14) and anti-hepatotoxic effect.15) However, there are few pharmacological studies of other compounds except ours. We previously performed an in vitro assay for 1, brazilein, 2, 3, 4, and 5, and clarified such properties as inhibition of nitric oxide (NO) production and inducible NO synthase gene expression, as well as free radical scavenging and antioxidant activity.…”
mentioning
confidence: 85%
“…[4][5][6][7][8][9] Pharmacological studies of Sappan Lignum focusing on its vasorelaxation 10) or immunosuppressive effect 11) have concluded that 1 is the active compound. Compound 1 alone was reported to show anti-inflammatory effect, 12,13) lensaldose reductase inhibitory effect, 14) and anti-hepatotoxic effect.…”
Section: )mentioning
confidence: 99%
“…1) and brazilin; the basic structures of the two contain a 3,4-cycloalkyl-fused benzopyran unit. In addition to this, they are known to possess anti-inflammatory activity, inhibit the lens-aldose reductase, and decrease the blood glucose level [1112]. Moreover, compound 3 was shown to inhibit HIV-1 integrase [1314].…”
Section: Introductionmentioning
confidence: 99%
“…For example their antimicrobial activities against Salmonella typhosa, Staphylococcus aureus, Brucella suis, and Shigella flexneri have been described (Pratt and Yuzuriha, 1959). Brazilin is also known to inhibit enzymes such as NO synthase (Sasaki et al, 2007), xanthine oxidase (Nguyen et al, 2005), protein kinase C (Kim et al, 1998), and aldose reductase (Moon et al, 1985). Methyl gallate and gallic acid also showed good antimicrobial activity against Bacillus subtilis ATCC 9372 and Staphylococcus aureus MRSA ATCC 33591 (Kubo et al, 2003(Kubo et al, , 2004.…”
Section: Resultsmentioning
confidence: 99%